Engineering microstructure of hydroxyapatite by electron beam irradiation to induce controllable in vitro degradation - Zhu, Hui; Zheng, Kai; Guo, Dagang; Zang, Hang; Yu, Sen; Xu, Kewei (Applied Surface Science, 2020)
Controllable degradation behavior of hydroxyapatite (HA) plays a crucial role in successful long-term implantation of a bone tissue substitute. In this study, electron beam irradiation (EBI) was carried out as an efficient strategy to modify HA structure. The degradation characteristics, bioactivity and cell response of the irradiated HA were comprehensively evaluated. The results showed that EBI with absorbed dose of 3.42, 10.27 and 20.54 Gy did not introduce newly-formed phase or impurity, but created crystal defects and nanovoids, which were formed from oxygen deficiencies, into HA lattice with irradiation dose-dependence. The dissolution rate of the irradiated HA enhanced continuously with increasing irradiation dose, as a result of constantly increasing crystal defects and enlarging voids, where the main reactive sites for the degradation of HA formed. The Ca2+ and PO43- releasing of HA with the highest irradiation dose enhanced by 92.75% and 138.85% respectively compared to that of the pristine HA after 28 days’ immersion. SBF immersion results suggested the irradiated HA with raising EBI doses exhibited preferable performance in bioactivity as well. Moreover, the results from CCK-8 assay and SEM observation showed that the irradiated HA were beneficial to the proliferation and attachment of osteoblasts.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Cell compatibility; Crystal defect; Electron beam irradiation; Hydroxyapatite; In vitro dissolution